Olympic weightlifting training causes different knee muscle-coactivation adaptations compared with traditional weight training - Arabatzi, F.; Kellis, E. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to compare the effects of an Olympic weightlifting (OL) and traditional weight (TW) training program on muscle coactivation around the knee joint during vertical jump tests. Twenty-six men were assigned randomly to 3 groups: the OL (n = 9), the TW (n = 9), and Control (C) groups (n = 8). The experimental groups trained 3 d·wk-1 for 8 weeks. Electromyographic (EMG) activity from the rectus femoris and biceps femoris, sagittal kinematics, vertical stiffness, maximum height, and power were collected during the squat jump, countermovement jump (CMJ), and drop jump (DJ), before and after training. Knee muscle coactivation index (CI) was calculated for different phases of each jump by dividing the antagonist EMG activity by the agonist. Analysis of variance showed that the CI recorded during the preactivation and eccentric phases of all the jumps increased in both training groups. The OL group showed a higher stiffness and jump height adaptation than the TW group did (p < 0.05). Further, the OL showed a decrease or maintenance of the CI recorded during the propulsion phase of the CMJ and DJs, which is in contrast to the increase in the CI observed after TW training (p < 0.05). The results indicated that the altered muscle activation patterns about the knee, coupled with changes of leg stiffness, differ between the 2 programs. The OL program improves jump performance via a constant CI, whereas the TW training caused an increased CI, probably to enhance joint stability.